Consumption patterns of clothing imitation in Metro Manila - Valera, Lerma Lynn S.
This study sought to determine the consumption patterns of clothing imitations in Metro Manila, price taken as a major factor affecting consumer behavior. The specific objective were as follows. 1. To find out what other factors affect the consumption patterns of consumers of clothing imitations. 2. To determine the extent which these factors affect consumers' choices. 3. To review the government policies relating to clothing imitations. 4. To find out the effects of the policies on consumption of clothing imitations. The study sought to prove the hypotheses that: price is a major determining factor in consumer's choice of buying clothing imitation; and, aesthetic attributes of both original brands/designer clothes are approximately he same. The descriptive method of research was adopted using the questionnaire checklist as the main instrument for data gathering. Eighty-six respondents consisting of 44 UP (University of the Philippines) students, 22 of whom are male and 22 are female, and 42 NEDA (National Economic and Development Authority) employees, 19 of whom are male and 23 are female, comprised the population of the study. Two methods of analysis were used: quantitative and qualitative. Analysis of data employed the averaging technique, percentage and rank. The study revealed that respondents are mostly single young catholics from Luzon with either a monthly allowance of less than P3,000 or a monthly income of P9,000 up to 12,000. The respondents buy knock-off or adaptation or line-for-line copy. According to them, price is the main reason for buying such clothes. Although, aesthetic and utilitarian qualities of clothing, especially style and comfort, also affect their buying decision. The similarity between clothing imitations and original brands/designer clothes in terms of aesthetic and utilitarian qualities also affect their buying decision very much. It was also found that most of the respondents are unaware of any government policy that regulate clothing imitations such as fake branded clothes or imitations, in general. The government policies related to imitations are that of the Intellectual Property Rights. In all, it could be concluded that price is a major determining factor in buying clothing imitations. Aesthetic and utilitarian qualities of clothing are also determining factors. More so, the similarity between clothing imitations and original brands/designer clothes in terms of aesthetic and utilitarian qualities of clothing is perceived as a major determining factor in buying clothing imitations. Also, the government policies on imitations, specifically relating to intellectual Property Rights, did not affect the respondents' decision to buy fake branded clothes. Recommendations could be that the owners of fashion lines should think of ways to get these consumers to patronize their products. Information on Intellectual Property Rights should be launched. Future researches may be conducted on the production and distribution patterns of clothing imitation; and also, on the consumption patterns of fake branded clothes.